Communication factors contributing to the success of film production in independent and mainstream film industry in Malaysia - Perumal, Vimala (2016)
Films are the joint creation of a huge number of individuals, each contributing with creative ideas, unique talents, and technical expertise to the project. Significantly,filmmaking is a collaborative process that derives from a good team effort achieved through effective communication. It is an undeniable fact that films are part of social institutions. In today‘s globalized and competitive environment, the strong focus on the successful independent and mainstream film is based on the assumption that there are strong relationships among the filmmakers/crewmembers. The Malaysian film industry presents a unique environment to study the crewmembers‘ behavior. Everything that is noticed on the screen is the finished product that results from decisions made by filmmakers during the production process, all of which will have involved some kind of interaction. Based on this strong relationship among the crewmembers, this study has been designed to assess and propose the appropriate communication factors among successful filmmakers/crewmembers in the successful independent and mainstream film industry environment. There are six possible predictors proposed in this study to identify the communication factors such as commitment, sharing ideas or experiences,trust, cohesiveness, collaboration and friendly relationship among crewmembers in the film industry atmosphere from the perspective of three communication theories: social exchange theory (SET), social penetration theory (SPT), and social constructive theory (SCT). This study is conducted with crewmembers that have worked on an international award-winning film production. The study is inclined toward a total of thirty-one successful films that were produced between 2000 and 2013. The survey involved 239 crewmembers from 24 independent film productions and 64 crewmembers from seven mainstream film productions. Data have been analyzed using SPSS for descriptive analysis and significant differences analysis. Based on the study, it was found that there is a significant relationship between the proposed predictors and successful films. There are four factors that contribute to the success of an independent film production, which are commitment, trust, collaboration and friendly relationship as compared to mainstream film production, which are trust and collaboration among the crewmembers. The findings indicate that every crewmember working in the independent film industry is more committed to the ideas and vision of the film production. Thus, the findings on factors affecting the crewmembers‘ communication are vital to ensure the continuous growth of quality films in the industry. This will help Malaysian film production companies to prepare more effective strategies to understand crewmembers‘ needs. In addition, academic institutions may also use this as a guideline for nurturing new talent among the young by instilling the importance of human communication and raising awareness that technical aspects in filmmaking alone are not sufficient to produce a good and quality film. This will make the process easier, especially in bridging the gap between theory and practice. Furthermore, the industry can utilize the results to provide a more productive environment for filmmaking, particularly in Malaysia, which is followed by most successful film production studios.